Mineral Physics-In Memory of Orson Anderson - Liebermann, Robert Cooper (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue contains original scientific papers in the field of mineral physics (and also rock physics). These papers are grouped into four categories: Reviews, Experimental Science, Theoretical Science and Technological Developments. These papers include those from first authors covering 5 generations of mineral physicists, including contemporaries of Orson [e.g., William Bassett, Frank Stacey], the next generation of leaders in mineral physics throughout the world [e.g., Michael Brown, Eiji Ohtani], current leaders in this field [e.g., Agnes Dewaele, Jun Tsuchiya], senior graduate students [e.g., Jan Borgomano, Vasilije Dobrosavlijevic, Francesca Miozzi], and an undergraduate student [e.g., Tyler Perez]. Mineral physics is the study of mineralogical problems through the application of condensed matter physics. In reality, mineral physicists use not only physics, but also solid-state chemistry; they study not only minerals, but all materials related to natural minerals (e.g., structural analogs, but also glasses, melts and fluids). Mineral and rock physics is intimately connected to many other geoscience disciplines including seismology, planetary science, petrology, geochemistry, geomagnetism, and geodynamics, and even materials and climate science. This book is dedicated to Orson Anderson who died in June 2019 at the age of 94.